The role of prosody for the expression of illocutionary types. The prosodic system of questions in spoken Italian and French according to Language into Act Theory - Cresti, Emanuela; Moneglia, Massimo (Frontiers in Communication, 2023)
The paper presents a corpus-based study of the correlations between prosodic contours and question speech acts in Italian and French from the perspective of the Language into Act Theory (L-AcT). A rich taxonomy of question illocutionary types is derived from two comparable corpora of informal speech taken from the C-ORAL-ROM collection and illustrated through prototypic examples. The number of questions in speech is evaluated as less than 10% of utterances. Despite their syntactic and accentual differences, the two languages share comparable pragmatic values conveyed by defined prosodic variations. Total questions, which can be answered with yes or no, are expected with canonical rising contours. Still, a good percentage shows so-called declarative prosody (26% in FR and 36% in IT). They have been supposed to be biased by presupposing the proposition's truth and have been considered Requests for confirmations instead of genuine Seeking for information acts. But presupposition, depending on intentional states, is hard to be detected, and no clear linguistic correlation was found. The corpus-based study of the prosody /pragmatics relation allows a better understanding of the system. Total questions should be framed within the larger category of Directives aimed at linguistic behavior, which does not foresee seeking information as the only goal. When the speaker makes a hypothesis on what he asks – that is not an actual presupposition – he performs a Request for confirmation. This is the case in most Total questions, and prosody complies with the canonical contour. In contrast, declarative contours correlate with corpus contexts in which the speaker does not make any hypothesis but puts pressure on the addressee (Challenging Questions). Partial questions genuinely seek information and comprise Open questions, which are verbless utterances where the addressee is requested to freely provide information on a given topic. Tag questions, Double questions, and Alternative questions correspond to Illocutionary patterns that, according to L-AcT, are composed of two pragmatic units framed within one prosodic strategy.